Dampak Konflik Rusia – Ukraina terhadap Pariwisata Rusia - Bestari, Ni Made Prasiwi; Sushanti, Sukma; Nugraha, A.A Bagus Surya Widya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2017)
ABSTRACT Intervention of Russia to Ukraine at the end of 2013 has caused a long period of conflict. This conflict has given impacts on social, economics and political sectors in both countries. This research analyzes the impacts of Russia and Ukraine conflict on Russia’s tourism industry in 2013 – 2015. This issues discussed by answering question to what extend Russia and Ukraine conflict caused impacts to Russia’s tourism sector. Data for this study were collected from various sources including, literary sources, news and reports. Data were analyzed with tourism studies in international relations and foreign policy theoretical frameworks. The analysis shows that the Russia – Ukraine conflict does not only give a serious impact on the socio-political life, but also affect the tourism sector of Russia. These occurred because there have been strong reactions against the Russia’s intervention by the international community in the form of economic sanctions and travel warnings. Russia’s decline in the tourism sector after the outbreak of the conflict shows that the tourism sector is integrated with international relations. Keywords: conflict, Russia’s tourism, economic sanctions, travel warning